Pengaturan Dan Pengawasan Praktik Kursus Veneer Gigi Pada Salon Kecantikan Di Indonesia - Alya Hasna Yogasara; Nyulistiowati Suryanti; Rai Mantili (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The aesthetic practice of dental veneers is rapidly becoming popular in Indonesia regardless of their economic background. High market demand if offset by very low prices can guarantee a large turnover. So this has given rise to many new business people who are interested in getting certification of expertise through dental veneer courses that do not have valid certificates and permits from the government. The purpose of this research is to determine the regulation and supervision of beauty salons that offer dental veneer courses. This research, which was carried out in this writing, uses normative juridical research methods with basic materials obtained through primary and secondary legal materials. Based on the research results, it can be concluded two things. First, Veneer Course Providers use materials and curricula that are not in line with dental medical standards so that the organizers of this non-formal education unit can be criminally charged regarding misappropriation of education provision in Article 71 and Article 67 paragraph 1 of Law No. 20 of 2003 Concerning the National Education System. Second, the government has a legal product of supervision of formal education units, namely in Article 66 of Law Number 20 of 2003 concerning the National Education System and regarding the running of beauty salons in the Regulation of the Director General of Nutrition and Maternal and Child Health Number HK.01.01/BI.4 /4051/2011 Concerning Guidelines for Organizing Beauty Salons in the Health Sector. However, in practice it is still necessary to increase government action, bearing in mind that dental veneer courses by beauty salons are a source of problems for the emergence of non-certified dental veneer businesses in the community.